Al-Fatihin: Islamic State's first Malay language newspaper - Singh, Jasminder (2016)
The so-called Islamic State (IS) has just released its first newspaper in the Malay Language, and declared in it a wilayah (province) in the Philippines. The publication of a Malay-language IS newspaper would have implications not only on Malay-speaking IS fighters in Iraq and Syria but also the Malay-speaking world in Southeast Asia.